A systematic review of sensors to combat crime and routes to further sensor development - Alice E. Cozens; Alice E. Cozens; Alice E. Cozens; Shane D. Johnson; Tung-Chun Lee; Tung-Chun Lee (Frontiers in Chemistry)
Forensic science plays an important part in crime reduction but faces many challenges. These include the validity, cost and complexity of current sensors used, and a reliance on trained professionals to conduct analyses. Recent advances in sensor technologies present a promising opportunity for rapid, decentralized, and cost-effective analysis by untrained individuals in the field. To date, a comprehensive systematic review covering sensing technologies and use cases has been lacking. This paper addresses that gap. After the initial screening of papers, 1,482 publications were included in the review, from which data on target analytes and sensing technologies were extracted. Given that law enforcement have limited resources, a second screening examined papers that focused on low-cost sensing devices published from 2020 onwards (N = 791). Overall, our review identified eleven key analyte categories that had been researched: illicit drugs, fingerprints, explosives, body fluids, food safety, poisons and toxins, pollutants, counterfeits and documentation, fire, gunshot, and others. Low-cost sensing technologies identified were categorised into electrochemical, colourimetric, immunoassay, luminescence and SERS. We review trends in the research reported, barriers to commercialisation and adoption, and review the use of these types of sensors by law enforcement agencies. Current sensors used by authorities face challenges of high costs, specificity issues, limited detection capabilities and complex sample preparation. Emerging research focuses on cost-effective printed electrodes and dual detection techniques to enhance analyte sensitivity and detection accuracy. Notably, body fluid analysis plays a crucial role in criminal cases, but current sensors suffer issues like false positives, DNA degradation, and high costs. Studies investigating eco-friendly materials and dual-detection approaches show promise in addressing these issues. Illicit drug analysis constitutes over one-third (36%) of included publications. In the UK, police rely on NIK tests and DrugWipe sensors for on-site drug detection, but challenges related to sensitivity, specificity, and confirmatory testing persist. Ongoing research explores dual detection methods, lateral flow immunoassays, and electro-chemiluminescent screening to enhance specificity and matrix tolerance. Future efforts should prioritise refining dual detection methods, reducing matrix interference, low-cost/eco-friendly materials and fostering collaboration between academia and law enforcement for effective implementation in these areas.